Mycobacterium tuberculosis multi‐drug‐resistant strain M induces IL‐17+IFNγ– CD4+ T cell expansion through an IL‐23 and TGF‐β‐dependent mechanism in patients with MDR‐TB tuberculosis. (2nd November 2016) - Basile, J. I.; Kviatcovsky, D.; Romero, M. M.; Balboa, L.; Monteserin, J.; Ritacco, V.; Lopez, B.; García, C. Sabio y; García, A.; Vescovo, M.; Montaner, P. G.; Palmero, D.; et al.
Summary: We have reported previously that T cells from patients with multi‐drug‐resistant tuberculosis (MDR‐TB) express high levels of interleukin (IL)‐17 in response to the MDR strain M (Haarlem family) of Mycobacterium tuberculosis ( M. tuberculosis ). Herein, we explore the pathways involved in the induction of Th17 cells in MDR‐TB patients and healthy tuberculin reactors [purified protein derivative healthy donors (PPD + HD)] by the M strain and the laboratory strain H37Rv. Our results show that IL‐1β and IL‐6 are crucial for the H37Rv and M‐induced expansion of IL‐17 + interferon (IFN)‐γ – and IL‐17 + IFN‐γ + in CD4 + T cells from MDR‐TB and PPD + HD. IL‐23 plays an ambiguous role in T helper type 1 (Th1) and Th17 profiles: alone, IL‐23 is responsible for M. tuberculosis ‐induced IL‐17 and IFN‐γ expression in CD4 + T cells from PPD + HD whereas, together with transforming growth factor (TGF‐β), it promotes IL‐17 + IFN‐γ – expansion in MDR‐TB. In fact, spontaneous and M. tuberculosis ‐induced TGF‐β secretion is increased in cells from MDR‐TB, the M strain being the highest inducer. Interestingly, Toll‐like receptor (TLR)‐2 signalling mediates the expansion of IL‐17 + IFN‐γ – cells and the enhancement of latency‐associated protein (LAP) expression in CD14 + and CD4 + T cells from MDR‐TB, which suggests that the M strain promotes IL‐17 + IFN‐γ – T cells through a strong TLR‐2‐dependent TGF‐β production by antigen‐presenting cells and CD4 + T cells. Finally, CD4 + T cells from MDR‐TB patients infected with MDR Haarlem strains show higher IL‐17 + IFN‐γ – and lower IL‐17 + IFN‐γ + levels than LAM‐infected patients. The present findings deepen our understanding of the role of IL‐17 in MDR‐TB and highlight the influence of the genetic background of the infecting M. tuberculosis strain on the ex‐vivo Th17 response. Abstract : M. tuberculosis (Mtb) multidrug resistant strain M induces differential expansion of IL‐17 + T cell subsets in patients with MDR‐TB: IL‐1β and IL‐6 secreted by Mtb stimulated APCs are crucial for IL‐17 secretion and IL‐17 + T cell expansion in MDR‐TB and PPD + healthy donors (HD). Particularly, in PPD + HD, Mtb induce the expansion of IL‐17 + IFNγ + cells through a TLR‐4 and IL‐23‐dependent mechanism, independent of the strain. In the case of MDR‐TB patients, recognition of MDR strain M via TLR2 induces APCs and CD4 + T cells binding LAP/TGF‐β complex (LAP) to secrete large amounts of TGF‐β that, in concert with IL‐23, supports the expansion of IL‐17 + IFNγ − CD4 + T cells which are responsible for the high Th17 response observed in MDR‐TB patients.